Utilization of accelerator and reactor based nuclear analytical techniques for chemical characterization of automobile windshield glass samples and potential of statistical analyses using trace elements towards glass forensics. (May 2022) - Sharma, V.; Sarkar, Arnab; Acharya, R.; Bagla, Hemlata K.; Pujari, P.K.
Highlights: Chemical characterization of automobile windshield glasses for forensic studies. External (in-air) PIGE using Ta as an external current normalizer for the quantification major (low Z) elements. INAA using high reactor neutron flux for quantification of trace elements: transition and rare earth elements. Quality assessment by analyzing the glass standard reference material (SRM). Utilization of trace elemental concentrations for grouping studies by statistical analyses for forensic applications. Abstract: Glass forensics is an important area in forensic crime investigations, wherein glass origin or source finding is necessary mainly through chemical composition. In the present work, Nuclear Analytical Techniques namely external (in air) Particle Induced Gamma-ray Emission (PIGE) and Instrumental Neutron Activation Analysis (INAA) were utilized for complete chemical characterization of twenty-five "as received" windshield glass samples of six car manufactures. Concentrations of four major elements (Si, Na, Mg and Al) by PIGE using proton beam and nineteen elements including sixteen trace elements by INAA using research reactor neutrons were determined. Both the methods were validated by analysing matrix matched glass certified (standard) reference materials. Trace elemental concentrations including rare earth elements (REEs) and ternary plot using concentrations of major, transition elements and REEs were utilized to obtain preliminary grouping of the analyzed glass samples. Statistical tools namely K-mean, Cluster Analysis and Principal Component Analysis (PCA) using trace elemental concentrations were utilized for grouping studies, important for forensic applications. Among these statistical analysis techniques, PCA results confirmed that windshield glasses from six manufactures clearly belong to six different groups.